O desenvolvimento profissional de professores do 1º ao 5º ano do ensino fundamental em um processo de formação para o ensino e a aprendizagem das medidas de tendência central - Lemos, Maria Patrícia Freitas de (2011)
The following review aims to investigate what comprehension and educational and didactical development of the content can be identified in teachers that operate in basic education from the first to the fifth school year on the Measures of Central Tendency, from the investigation of their professional development on a continuous graduation. For so, we structured the review in three theoretical moments that organise our bibliographical review: a review of the studies on Measures of Central Tendency that allowed us to identify the obstacles faced by the students and teachers, and a discussion about the teacher's professional development. The methodological process of the research was structured in five stages distributed as follows: the first stage is the settlement of a teaching sequence in a Statistics course arranged in five meetings; the second stage is the elaboration of a task; the third stage is the analysis of the task elaborated; the fourth stage is the implementation of the task in classroom; and the fifth stage is the completion of the analysis process and discussion about the implementation of the task in classroom and the whole process of intevention experienced. Six teachers who taught from the first to the fifth school year of the basic education in the city of São Paulo participated in this study in the period of the development of the project. The results showed that the initial difficulties identified in the protocols built with dialogues and productions of the teachers, in the comprehension of the concepts of median, mode and media and of their properties, were overcome during the process, though the global analysis showed graduation insufficiency to the achievement of this conceptual construction. With respect to the elaboration and analysis of the task, we realised that the teachers had trouble in enunciating the contents of median, mode and media, not identifying the properties, the kind of variant involved in the task and their influence in the development of the task in classroom. In the analysis of a task elaborated by them, the teachers also showed lack of articulation, master and knowledge of the content. The implementation of the task in classroom took place as a positive moment in which the teachers could see not only the good performance of the students, but also could reconsider their conceptions and attitudes towards the Statistics, which was reinforced in the stage destinated to the analysis and discussion about the whole process of intervention. We came to the realisation that the teachers could enlarge their professional development not only in what comes to the contents of the Measures of Central Tendency, but in their conceptions, attitudes and educational knowledge of the content, admitting their difficulties and realising the importance of a continuous graduation process